The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1056/nejm198510173131603
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing Antiepileptic Medication in Children with Epilepsy after Two Years without Seizures

Abstract: Antiepileptic medications were discontinued in 88 children with epilepsy of various causes who had been free of seizures for two to four years. The subjects were then followed for six months to five years (mean, 22 months). Sixty-six (75 per cent) remained free of seizures. Electroencephalographic characteristics, type of seizure, and age at onset were important in predicting outcome. Specific electroencephalographic features (such as the presence or absence of slowing or spikes) were more predictive than simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
105
4
7

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 17 publications
8
105
4
7
Order By: Relevance
“…Berg and Shinnar reported that the epilepsies, which began before 12 years od age, had higher rate of seizure relapse risk than those after 12 years of age [30]. Shinnar et al also reported that the mean age of epilepsy was 6.9 years in patients who had seizure relapse and 4.3 years in patients who did not have seizure relapse [31]. In our study, we found that age at theonset of epilepsy (especially >5 years), the total number of seizures (especially >5 seizure), new seizure during treatment, and the need for polytherapy were important risk factors for seizure relapse after AEDs withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Berg and Shinnar reported that the epilepsies, which began before 12 years od age, had higher rate of seizure relapse risk than those after 12 years of age [30]. Shinnar et al also reported that the mean age of epilepsy was 6.9 years in patients who had seizure relapse and 4.3 years in patients who did not have seizure relapse [31]. In our study, we found that age at theonset of epilepsy (especially >5 years), the total number of seizures (especially >5 seizure), new seizure during treatment, and the need for polytherapy were important risk factors for seizure relapse after AEDs withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…We had a similar yield of abnormal report in EEG. There is wide variation in sensitivity (23%-77%) and specificity (24%-99%) of reported EEG in general population [58][59][60][61][62][63][64][65][66][67] . Donald L et al 68 concluded three important findings related to wide variation in sensitivity and specificity of EEG.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that this factor has shown only a tendency towards significance 22,23 . Moreover, others showed no relationship between number of seizures prior to seizure control and increased recurrence risk for seizure recurrence after discontinuation of AED [24][25][26] . However, the importance of these studies might be limited to patients at tertiary epileptic centers, since seizures are easily controlled in a great majority of the patients with recently diagnosed epilepsy 7 .…”
Section: Discussionmentioning
confidence: 99%